The Role of Financial Report Analysis in the Efficiency and Effectiveness of Financial Performance - Audi Elshinta Gading; Mustaqiem Arja; Fadia Ananda; Galih Supraja (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze the influence of effectiveness and efficiency in financial management at the village and regional levels. The main focus of this research is to evaluate how the financial management system implemented can affect the effectiveness of achieving financial goals and efficiency in budget use. The method used in this research is a literature review method that examines various journals related to village and regional financial management. This approach is done by collecting, comparing, and analyzing the findings of five relevant journals. From the results of the analysis, it was found that although effectiveness in achieving financial objectives tends to be high, efficiency in budget use still faces major challenges. Factors affecting low efficiency include limited human resource capacity, weak supervision, and mismatches between budget planning and execution. This research also shows that transparent and structured financial management systems, such as SISKEUDES, can improve management effectiveness, but do not guarantee optimal efficiency without improvements in human resource training and supervision. As a suggestion, increasing the capacity of financial managers, strengthening the supervision system, and increasing transparency at every stage of budget management are essential to achieve more efficient goals.